Fundamentals of enterprise risk management : how top companies assess risk, manage exposures, and seize opportunities - Hampton, John J. (New York : American Management Association, 2009)
The book offers an expansive yet focused approach that will radically improve your ability to recognize risk and minimize loss, as well as understand the level of risk that's required to pursue opportunities. Comprehensive, refreshingly clear, and packed with the latest insights from the field, the book is essential reading for anyone responsible for monitoring risk exposures, in any setting-corporate, nonprofit, or government.
Includes bibliographical references and index.
rpm 24/05/13
Loans
Keywords: Corporations; Risk assessment; Risk management